Analisis Kebutuhan Desain Perangkat Pembelajaran Berbasis Scientifics dalam Mencapai Academic Success Skill - Motlan, Motlan; Sinuraya, Jurubahasa; Sinulingga, Karya; Mihardi, Satria (Universitas Sebelas Maret, 2017)
Abstract:. Learning tools are an important part of a lecture. Consistency in both formatting and quality design becomes an important role. In this study aimed at the development of Scientifics-based device design approach. Improved Academic Success Skill becomes the ultimate goal of application of the resulting device design. The research method used is based on product development. In the research conducted information gathering through questionnaires and needs analysis in various faculties. There are 3 stages in the research through the product observation stage, survey needs analysis, and responsive questionnaire. From the research results obtained that: First, the product produced so far has not been directed to the achievement of Academic Success Skill and arranged in a standard format and intact; Secondly, consistency and standard in producing instructional tools that become the benchmark is felt necessary in supporting the alignment and suitability to support the performance of lectures; and Third, the need for the format and design of standard and specific learning tools on the achievement of Academic Success Skill is expected to materialize in assisting the implementation of more co-ordinated courses. In subsequent developments the model of learning device design is tested in small groups that will be used as information in the improvement and analysis of deficiencies to the resulting product. Abstrak: Perangkat pembelajaran merupakan bagian penting dari suatu pelaksanaan perkuliahan. Konsistensi dalam perancangan baik secara format dan kualitas menjadi peranan penting. Dalam penelitian ini ditujukan pada pengembangan desain perangkat berbasis pendekatan Scientifics. Peningkatan Academic Success Skill menjadi tujuan akhir penerapan desain perangkat yang dihasilkan. Metode penelitian yang digunakan berlandaskan pengembangan produk. Dalam penelitian dilakukan pengumpulan informasi melalui angket dan analisis kebutuhan diberbagai fakultas. Ada 3 Tahapan dalam penelitian melalui tahapan observasi produk, survey analisis kebutuhan, dan angket responsif. Dari hasil penelitian diperoleh bahwa: Pertama, produk yang dihasilkan selama ini belum terarah kepada pencapaian Academic Success Skill dan tertata dalam format yang baku dan utuh; Kedua, Konsistensi dan standar dalam menghasilkan perangkat pembelajaran yang menjadi patokan sangat dirasakan perlu dalam menunjang keselarasan dan kesesuaian untuk menunjuang kinerja perkuliahan; dan Ketiga, kebutuhan format dan desain dari perangkat pembelajaran yang baku dan spesifik pada pencapaian Academic Success Skill sangat diharapkan terwujud dalam membantu pelaksanaan perkuliahan yang lebih terkoordirnir. Dalam perkembangan selanjutnya model desain perangkat pembelajaran diujikan dalam kelompok kecil yang akan dijadikan informasi dalam perbaikan dan analisis kekurangan terhadap produk yang dihasilkan.